2016
DOI: 10.1002/smll.201601484
|View full text |Cite
|
Sign up to set email alerts
|

AIEgens‐Functionalized Inorganic‐Organic Hybrid Materials: Fabrications and Applications

Abstract: Inorganic materials functionalized with organic fluorescent molecules combine advantages of them both, showing potential applications in biomedicine, chemosensors, light-emitting, and so on. However, when more traditional organic dyes are doped into the inorganic materials, the emission of resulting hybrid materials may be quenched, which is not conducive to the efficiency and sensitivity of detection. In contrast to the aggregation-caused quenching (ACQ) system, the aggregation-induced emission luminogens (AI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(53 citation statements)
references
References 151 publications
(206 reference statements)
1
52
0
Order By: Relevance
“…Silica nanoparticles (SNs) have been intensively pursued over the past few decades owing to their fascinating features and properties, which include ideal chemical stability, rigid structure, uniform and tunable pore structure, facile surface functionalization, and good biocompatibility . Silica received the “generally recognized as safe” status designated by the U.S. Food and Drug Administration (FDA), as demonstrated by its common use in food additives and vitamin supplements . In particular, mesoporous silica nanoparticles (MSNs) are widely employed as promising candidate carriers for drug delivery and as building blocks for stimuli‐responsive systems .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Silica nanoparticles (SNs) have been intensively pursued over the past few decades owing to their fascinating features and properties, which include ideal chemical stability, rigid structure, uniform and tunable pore structure, facile surface functionalization, and good biocompatibility . Silica received the “generally recognized as safe” status designated by the U.S. Food and Drug Administration (FDA), as demonstrated by its common use in food additives and vitamin supplements . In particular, mesoporous silica nanoparticles (MSNs) are widely employed as promising candidate carriers for drug delivery and as building blocks for stimuli‐responsive systems .…”
Section: Introductionmentioning
confidence: 99%
“…These integrated nanosystems provide new degrees of freedom to control the functionality of nanoparticles. [1c], [2b] In this context, the combination of hollow mesopores and fluorescence properties into one nanostructure has attracted great interest owing to the enormous potential of these materials in the construction of complex nanoplatforms and, ultimately, multifunctional materials . Different from conventional fluorescent dyes, aggregation‐induced emission (AIE) molecules possess characteristics that are opposite to those of aggregation‐caused quenching (ACQ) molecules and are an important and novel category of fluorogens that emit more efficiently in the aggregated state than in the dispersed state.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past few years, considerable efforts have been devoted to the design and synthesis of AIEgens‐MOFs and the exploration of their applications. In some review articles, AIEgens‐MOFs have been mentioned. For example, Tang et al reported a comprehensive AIE related review article, which contains AIEgens‐MOFs .…”
Section: Introductionmentioning
confidence: 99%
“…Aggregation‐induced emission luminogens (AIE‐gens), a class of recently developed organic luminescence materials, are nearly nonemissive in dilute solution but show strong fluorescent emission in aggregated states . Due to this unique luminescence behavior together with the excellent film‐forming property, they have been successfully applied in biomedicine, chemosensors, and LEDs .…”
mentioning
confidence: 99%